2004
DOI: 10.1117/12.535465
|View full text |Cite
|
Sign up to set email alerts
|

Registration of micro-PET and high-resolution MR images of mice for monitoring photodynamic therapy

Abstract: We are investigating imaging techniques to study the rapid biochemical and physiological response of tumors to photodynamic therapy (PDT). Positron emission tomography (PET) can provide physiological and functional images of cancers. While MRI can provide high resolution anatomical images and generate serial, noninvasive, in vivo observations of morphological changes. In this study, we investigate image registration methods to combine MRI and micro-PET (µPET) images for improved tumor monitoring. We acquired h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In our previous study, we used both MRI and positron emission tomography (PET) to image C3H mice bearing RIF-1 tumors after PDT [31,32]. PET with 18 F-fluorodeoxyglucose (FDG) provided metabolic information of the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we used both MRI and positron emission tomography (PET) to image C3H mice bearing RIF-1 tumors after PDT [31,32]. PET with 18 F-fluorodeoxyglucose (FDG) provided metabolic information of the tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The voxel size was 1.0 × 1.0 × 1.6 mm 3 . We registered the CT to the corresponding MR images using the registration methods [22][23][24][25][26][27][28] that have been evaluated in our laboratory. On the CT images, we used a threshold method to obtain the skull and the results provide the ground truth of the skull for the evaluation of the MR image segmentation.…”
Section: Iig1 Segmentation Evaluationmentioning
confidence: 99%
“…(1) We first register the MR images with the preliminary reconstruction of PET data using the mutual informationbased registration methods developed in our lab. [22][23][24][25][26][27][28] (2) The skull tissue is segmented on the MR images using our segmentation method as described below. (WM), and cerebrospinal fluid (CSF).…”
Section: Iic Overview Of the Mr/pet Data Processingmentioning
confidence: 99%
“…We found that the tumor FDG uptake decreased immediately after PDT. [11][12][13] In this study, we focus on small animal MR imaging and analysis methods for monitoring the efficacy of prostate PDT in vivo. To the best of our knowledge, this is the first report on in vivo imaging for Pc 4-based PDT for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a previous study, we used both MRI and positron emission tomography (PET) to image C3H mice bearing RIF-1 tumors after PDT. [11][12][13] PET with 18 F-fluorodeoxyglucose (FDG) provided metabolic information of the tumors. High-resolution MRI provided anatomical and morphological changes of the lesions.…”
Section: Introductionmentioning
confidence: 99%